Cytological description of testicular cell populations in sexually mature cats with normal spermatogenesis. Issue 10 (2nd August 2020) - Bodet, Lucile; Albaric, Olivier; Topie, Emmanuel; Dagher, Elie; Chocteau, Florian; Gogny, Anne
Abstract: In cats, assessment of the testicular function is mainly based on sperm evaluation. Whatever the technique used, the volume of collected sperm is often small, which may lead to technical difficulties to achieve the semen evaluation in routine practice. Fine‐needle aspiration (FNA) biopsy of the testicular parenchyma is one of the other methods used to assess testicular function. The aim of this study was to explore the relevance of FNA in the assessment of testicular cells in sexually mature cats. Eighteen cats over one year of age were recruited among animals presented for surgical neutering. Semen was collected by electroejaculation before it was evaluated. FNA biopsies of the testicles were taken using a 21‐gauge needle. After castration, histological analysis of the testes was performed. Semen evaluation and histological analysis showed no anomalies, which confirmed normal spermatogenesis in all the cats and allowed a proper interpretation of the cytological findings. The cells identified through cytological examination were spermatogonia (1.99 ± 0.17%), primary spermatocytes (10.49 ± 0.74%), round spermatids (34.80 ± 1.57%), elongated spermatids (23.59 ± 2.02%), spermatozoa (21.56 ± 1.86%), Sertoli cells (7.53 ± 1.23%) and Leydig cells (0.04 ± 0.03%). However, spermatocytes II were not identified. This is due to the low proportions of these cells, related to their very short lifespan. Likewise, the very low number of Leydig cells observed is probably due to the damage caused during the aspiration stage. This study showed that fine‐needle aspiration is an efficient method to describe cytologically normal testicular populations, a cornerstone for future research aimed to study abnormal spermatogenesis and to correlate it to cytological proportion of germ cells.